ANALISIS PELAKSANAAN PROGRAM LATIHAN PADA CABANG OLAHRAGA SEPAK BOLA BENTENG HB KOTA BENGKULU - Pratama, Pratama; Juwita, Juwita; Sumantri, Ajis (UNIVED Press, Universitas Dehasen Bengkulu, 2024)
This study aims to determine how the implementation of the football training program of Benteng HB Club Bengkulu City. This research uses Qualitative research methods. This research uses instruments in the form of questionnaires and interviews. The population in this study were 20 Benteng HB soccer players. The results of this study The training program is made by referring to the National Training Program Standards. In making training programs, the coach involves players in making football training programs. In the training program there are physical, technical and mental exercises. In implementing the training program, the coach refers to the previously made training program. In its implementation, all training programs are carried out by the Benteng HB football team.